Neuregulin1β improves both spatial and associative learning and memory in Alzheimer model of rats possibly through signaling pathways other than Erk1/2. (December 2019) - Jalilzad, Marzieh; Jafari, Adele; Babaei, Parvin
Abstract: Background: Neuregulin-1β (NRG1 β) is associated with various neurological disorders such as schizophrenia, depression and Parkinson's disease. However, its role in Alzheimer's (AD) has not been understood yet. Here, we have studied the effect of NRG1 β and extracellular-signal-regulated kinase (ERK) signaling on special and associative memories and emotional stress in AD model of rats. Methods: Fifty six male Wistar rats were divided into eight groups of: Saline + Saline, Aβ + Saline, Aβ + NRG1β (5 μg/5 ul), Aβ + PBS, Aβ + NRG1β + PD98059 (PD, 5 μg/2 μl), Aβ + NRG1β + Saline and Saline + PD. AD model was induced by intracerebroventricular (ICV) injection of beta-amyloid protein (Aβ1-42, 4 μg/2 μl). The cognitive performances of rats were evaluated using Morris Water Maze (MWM) and Step through passive avoidance. Also locomotors activity and emotionality of animals were considered in an Open field test. Data were analyzed by one way Anova one way, repeated measure and T-test. Results: Significant improvement was found in spatial learning and memory assessed by total time spent in target quadrant [F (4, 32) = 12.4, p = 0.001], escape latency [F (4, 32) = 15.767, p = 0.001] and distance moved [F (4, 32) = 5.55, p = 0.002], in Aβ + NRG1β compared with Aβ + Saline in MWM. Also Aβ + NRG1β showed long latencies to enter into the dark compartment [F (4, 32) = 6.43, p = 0.001], but short time spent [F (4, 32) =6.93, p = 0.001] compared with control. Administration of an ERK inhibitor (PD98059, 5 μg, 15 min before NRG1β) didn't completely block learning memory restored by NRG1β in AD model (p = 0.7). No significant between groups differences was found in emotional stress characteristics in open field, except the grooming numbers which were higher in Saline + PD compared with Saline + Saline (p = 0.02). Conclusion: Our findings indicate that NRG1β restores cognitive dysfunctions induced by amyloid β through signaling pathways possibly other than Erk1/2, with no significant change in anxiety, locomotion and vegetative activities. Highlights: Neuregulin1β improves both working and reference memories in Alzheimer's model of rat. Neuregulin1β improves associative long term memory in Alzheimer's model of rat. Nrg1β facilitates memory via signaling pathways possibly other than Erk1/2. NRG1β has no significant effect on measure of anxiety, locomotion and vegetative activities.